The Creation and Use of Open Educational Resources in Christian Higher Education - Hilton, John; Wiley, David A. (2009)
Open educational resources (OERs) represent a new frontier in eduction. There are several examples of individuals and institutions providing open educational resources; this openness is also specifically manifest in the field of Christian higher education. Different levels are discussed in which OERs can be “open” and the implications of these levels when creating OERs. Common motivations and obstacles to creating OERs are also discussed. A particularly significant issue regarding openness concerns copyright issues. Finally, discussed are copyright implications both in terms of reusing resources others have made (resources that may or may not be copyrighted), and using Creative Commons licenses to license OERs so as to give the desired level of copyright protection. Although OERs are not appropriate in all situations, they can be an important part of improving pedagogy and increasing access to education.